Penyuluhan Kesehatan Dan Pemantaun Kejadian Anemia Pada Remaja Putri di MTS Al Hidayah Desa Bedali Kecamatan Ngancar Kabupaten Kediri - Asiyah, Siti (STIKES dan AKZI Karya Husada Kediri, 2024)
Adolescent girls suffer from anemia if blood hemoglobin levels show a value of less than 12 gr/dl. 6 Around 30% of adolescents in developing countries suffer from anemia. The incidence of anemia in adolescent girls is due to the iron content of the food consumed being insufficient. This activity aims to provide understanding and also monitor the incidence of anemia in young women. The method used in implementation, cross-program collaboration with Nganjar Community Health Center and cross-sector with MTS Al Hidayah, Bedali Village, Ngancar District, Kediri Regency, implementation method with education and checking Hemoglobin levels, 12-22 September 2023 at MTS Al Hidayah, Bedali Village, Kediri Regency. Evaluation of activity results: 25% experienced anemia. The success of this service activity was due to support from the main partners in supporting educational facilities and places as well as efforts to encourage the participation of pregnant women in this activity.